Konflik Sosial Dalam Novel Children of Blood and Bone Karya Tomi Adeyemi - Safitri, Imas (PT. Alahyan Publisher Sukabumi, 2024)
The research is entitled Social Conflict In Children Of Blood And Bone Novel By Tomi Adeyemi. The method of this research is a Descriptive Qualitative Method and uses an Objective Approach. Data collection in this research uses reading and writing techniques The theory of the research uses the theory of Soekanto (2005); the theory of Class And Class Conflict in Industrial Society, Banks & Dahrendorf (1960); and theory of The Functions Of Social Conflict, Coser (1964). The purpose of this research is; (1) To describe social conflict in Children Of Blood And Bone novel by Tomi Adeyemi. The research found three kinds of social conflict in the novel; (1) personal conflict, (2) racial conflict, and (3) social class conflict.